Implementasi Strategi Komunikasi Lintas Budaya dalam Pelayanan Penginapan Lokal di Badung, Bali - Ni Ketut Arniti; Yustitia Widiasari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This research aims to analyze intercultural communication strategies and the effectiveness of communication within the service interactions at Bakung Beach Resort, Badung, Bali. The study is based on the increasing intercultural interactions between resort staff and international tourists, which require communication competencies capable of bridging differences in language, values, and communication styles. This research employs a qualitative approach using a case study method, utilizing in-depth interviews, field observations, and documentation. The findings reveal that the intercultural communication strategies implemented by the staff include the use of nonverbal expressions such as smiling, eye contact, and gestures, language adjustment through simple and clear sentences, and emotional management to maintain a comfortable interaction. Communication effectiveness is analyzed using Gudykunst’s Anxiety/Uncertainty Management (AUM) Theory, which consists of four indicators: predictive uncertainty, explanatory uncertainty, anxiety management, and effectiveness of message delivery. Results indicate that the staff successfully reduce uncertainty through careful observation of guest behavior, interpret guest intentions through clarification and nonverbal cues, and manage anxiety to maintain polite and professional service. Communication is considered effective as indicated by minimal misunderstandings, increased tourist comfort, and the creation of harmonious interpersonal relationships. This study concludes that cultural adaptability and the application of appropriate communication strategies play crucial roles in delivering high-quality services in a multicultural hospitality environment.